Metal-ion sensing and aggregation studies on reactive phthalocyanines bearing soft-metal receptor moieties; synthesis, spectroscopy and electrochemistry - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
Tetrasubstituted metal-free {2H[Pc(S(CH2)(6)OCOC4H3S)(4)]} and copperphthalocyanine {Cu[Pc(S(CH2)(6)OCOC4H3S)(4)]}, bearing thiophene-2-carboxylate-hexylthio moieties, have been prepared as isomeric mixtures via cyclo-tetramerization. Both new compounds have been characterized by elemental analysis, FTIR, H-1 and C-13 NMR, MS (Maldi-TOF) and UV-Vis spectral data, The cation binding abilities of the functional phthalocyanines with Ag-I, Pd-II, Hg-II, Pb-II and Cd-II are evaluated by a monomer-oligomer formation technique with U-V-Vis spectroscopy. Spectroscopic properties of the complexes were affected strongly by the electron-donating sulfanyl units on the periphery. Cyclic voltammetry and differential pulse voltammetry studies show that both compounds give up to three ligand based reduction processes and one ligand-based oxidation process having diffusion-controlled one electron transfer properties. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: phthalocyanine; metal-free; copper; silver; palladium; ion receptor; Maldi-TOF; Electrochemistry; METALLOPHTHALOCYANINES; NO2